Increased biting rate and decreased Wolbachia density in irradiated Aedes mosquitoes - Riccardo Moretti; Elena Lampazzi; Claudia Damiani; Giulia Fabbri; Giulia Lombardi; Claudio Pioli; Angiola Desiderio; Aurelio Serrao; Maurizio Calvitti (Parasites & Vectors, 2022)
Abstract Background Releasing considerable numbers of radiation-sterilized males is a promising strategy to suppress mosquito vectors. However, releases may also include small percentages of biting females, which translate to non-negligible numbers when releases are large. Currently, the effects of irradiation on host-seeking and host-biting behaviors have not been exhaustively investigated. Information is also lacking regarding the effects of sterilizing treatment on the endosymbiotic bacterium Wolbachia, which is known to affect the vector competence of infected mosquitos. Methods To ascertain the effects of irradiation on females, the pupae of two Aedes albopictus strains, differing in their natural or artificial Wolbachia infection type, and Aedes aegypti—which is not infected by Wolbachia—were treated with various doses of X-rays and monitored for key fitness parameters and biting behavior over a period of 2 weeks. The effect of radiation on Wolbachia was investigated by quantitative polymerase chain reaction (qPCR) and fluorescence in situ hybridization (FISH) analysis. Results Partial Aedes albopictus female sterility was achieved at 28 Gy, but the number of weekly bites more than doubled compared to that of the controls. Radiation doses of 35 and 45 Gy completely inhibited progeny production but did not significantly affect the survival or flight ability of Ae. albopictus females and caused a tripling of the number of bites per female per week (compared to untreated controls). These results were also confirmed in Ae. aegypti after treatment at 50 Gy. Wolbachia density decreased significantly in 45-Gy-irradiated females, with the greatest decreases in the early irradiation group (26 ± 2-h-old pupae). Wolbachia density also decreased as adults aged. This trend was confirmed in ovaries but not in extra-ovarian tissues. FISH analysis showed a strongly reduced Wolbachia-specific fluorescence in the ovaries of 13 ± 1-day-old females. Conclusions These results suggest that, under sterile insect technique (SIT) programs, the vector capacity of a target population could increase with the frequency of the irradiated females co-released with the sterile males due to an increased biting rate. In the context of successful suppression, the related safety issues are expected to be generally negligible, but they should be conservatively evaluated when large-scale programs relying on imperfect sexing and high overflooding release ratios are run for long periods in areas endemic for arboviral diseases. Also, the effects of irradiation on the vector competence deserve further investigation. Graphical Abstract